2011
DOI: 10.1002/ptr.3544
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Antiinflammatory Activity of Kaur‐16‐en‐19‐oic acid from Annona reticulata L. Bark

Abstract: Kaur-16-en-19-oic acid was isolated from the bark of Annona reticulata and studied for its analgesic and antiinflammatory activity. Analgesic activity was assessed using the hot plate test and acetic acid-induced writhing, and the antiinflammatory activity using the carrageenan induced rat paw oedema method. Kaur-16-en-19-oic acid, at doses of 10 and 20 mg/kg, exhibited significant (p < 0.05) analgesic and antiinflammatory activity. These activities were comparable to the standard drugs used, and furthermore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 18 publications
3
11
0
1
Order By: Relevance
“…We also hypothesized that treatment with the plant fractions also protects all the other major nerves from oxidative damage that affected in DNP condition. Previous reports on antioxidant and anti-inflammatory potential A. reticulata and Z. jujuba further strengthen the present study (Chavan et al, 2012a,b; Kandimalla et al, 2016a,e). Where, both plant bioactive fraction shows protection against DNP through reducing oxidative stress and inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 91%
“…We also hypothesized that treatment with the plant fractions also protects all the other major nerves from oxidative damage that affected in DNP condition. Previous reports on antioxidant and anti-inflammatory potential A. reticulata and Z. jujuba further strengthen the present study (Chavan et al, 2012a,b; Kandimalla et al, 2016a,e). Where, both plant bioactive fraction shows protection against DNP through reducing oxidative stress and inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 91%
“…considered to be supraspinally integrated responses (Chapman et al 1985;Chavan et al 2012). Crude extract and its polar fractions were shown to possess a significant analgesic effect on acetic acid inducing writhing test when compared to the control group and this in a dosedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…St.-Hil., and A. dioica A. St.-Hil., have confirmed their folk medicinal properties for the treatment of inflammatory disease (Chavan et al, 2010(Chavan et al, , 2011(Chavan et al, , 2012aDe Sousa et al, 2010;Formagio et al, 2013a,b;Yeo et al, 2011). Previous studies performed by our research group as well as others have shown that the extract, essential oil, and identified compounds obtained from the leaves and bark of Annona species exert anti-inflammatory and antinociceptive effects (Chavan et al, 2010(Chavan et al, , 2011(Chavan et al, , 2012aDe Sousa et al, 2010;Formagio et al, 2013a,b;Yeo et al, 2011).…”
Section: Discussionmentioning
confidence: 81%